Prinsip Dasar Tata Rupa Dalam Film Animasi “The Secret Of Kells” - Wahju Tri Widadijo (AKSA: Jurnal Desain Komunikasi Visual, 2020)
This article reviews the analysis of the application of the basicprinciples of visual arts and design in the animated movie “TheSecret of Kells” (2009) directed by Tomm Moore. The pictures andillustrations used in this animation is very unique and very artistic.The pictures and illustrations are created with the ornamental styleof the medieval art period. This study is based on the initialassumption, that is, one of the indicators of good animation is howthe impression of every cut of the film is influenced by artisticelements applied within the composition, the layout, and theblocking. In the staging aspect, as one of the aspects of 12 principlesof animation, it says that every visual asset in animation should belayouted properly to make a good and right composition. One of thestrategies is by applying the basic principles of visual arts anddesign such as rhythm, unity, domination, balance, and proportion.The analytical process itself was using a descriptive qualitativemethod. The purpose of this analysis is to show the intensity of theuse of the basic principles of visual arts and design in the animatedmovie “The Secret of Kells” (2009).